PERTUMBUHAN DAN HASIL TANAMAN KEDELAI (Glycine max (l) Merr) YANG DIBERI PUPUK KOTORAN KAMBING DAN RHIZOBIUM SP PADA TANAH GAMBUT - Winarti Sih; Sundari Yayang; Asi Yanetri (AgriPeat, 2016)
This study aimed to examine the response of soybean plants to organic fertilizer goat manure and Rhizobium sp on peat soil, and determine the goat manure fertilizer and Rhizobium sp which gives the growth and yield of soybean best in peat soil. This experiment used a block randomized factorial design with two factors treatments and 3 replications. The first factor is the goat manure consists of three levels ie 0 , 10 and 20 t ha-1 and the second factor is the Rhizobium sp consists of five levels ie 0 , 4 , 8 , 12 and 16 g kg-1 seed.The results showed that the highest number of root nodules on soybean obtained by goat manure dose of 20 t ha-1 and 12 g kg-1 seed Rhizobium sp. Fertilization goat manure at a dose of 10 t ha-1 on peat, soybean plants tend to grow taller, wider leaves, root nodule weight effectively, the weight of pods, seed weight per plant and 1000 grain weight was significantly higher and the real number of pods per plant more than in the controls. GivingRhizobiumspon peat soilwitha dose of12gkg-1seed, is capable of significantly increased plant height, leaf area, number of root nodules effectively, the weightof nodulesperplant, weightof pods perplant, seed weight perplant and weight of 1000 seeds of soybean compared with nogiven Rhizobiumsp (control)